Semences de blé ancien - Elisabetta Bucolo (Revue Internationale des Études du Développement)
The study of commons brings significant insights in economics, law, and sociology. It opens up space for an alternative to the mainstream economic doxa, to legal determinism, and to methodological individualism. It sheds light on the ability of stakeholders to “act together” and to join forces to assert forms of management, production, and consumption which are in line with the experience of a group of stakeholders or of territorial communities. In this sense, we have examined collectives working to preserve ancient wheat crops in Sicily to grasp the stakes linked to these initiatives and what they bring within the context of the international debate on biodiversity and food sovereignty.